MEASURING THE IMPACT OF AN INNOVATIVE EDUCATION PROGRAM IN AN ACADEMIC INSTITUTION FROM A PUBLIC UNIVERSITY IN MEXICO - Barajas-Villarruel, Juan Ignacio (European Scientific Journal, ESJ, 2014)
Since the implementation of the Innovative Education Program (PIEFCA in Spanish) in a public university in Mexico, it had not been assessed in terms of strengths, weaknesses and technological needs for the end users. Bearing that in mind, it was established that a research project was required in order to assess the degree to which its goals had been achieved. Three strategies were used to answer the research questions. Firstly, a content analysis was carried out. Then, a session was conducted with a focus group and lastly, they were asked to do a survey. The sample was probabilistic, with a total of 168 teachers. School authorities and other employees participated as well. Results indicate that one of the main strengths of the program is the people who work in it. On the other hand, one of the weaknesses was a shortage in staff to meet the needs of all the users. It is concluded that teachers evaluated the services offered by PIEFCA positively.)